Investigating Speaking Practice Using Estudy Moodle in Online Learning During Covid 19 Pandemic - Indah Werdiningsih (Universitas Muhammadiyah Jember, 2022)
It is crucial for educators to be creative in making new innovation for online learning – one of which is by utilizing the use of modern technology (Astini, 2020; Atsani, 2020) – especially for speaking skills where interaction among peers is needed. In online classroom where direct interaction is not possible, learning process must be carried out through a balance synchronous and asynchronous activities (Yamagata-Lynch, 2014). This study intends to investigate the speaking ability of the 5th semester students who use eStudy Moodle for online learning covering aspects of synchronous and asynchronous activity (using LMS and Google Meet video conference attached in eStudy). The method used is a combination of quantitative (speaking test) and qualitative research method (questionnaire). After analyzing the data, it was found that the speaking ability of the students can be categorized good (A-B) and most of them enjoyed online learning using eStudy. Their speaking ability is most likely achieved due to the convenience of learning speaking using eStudy. Despite the fact that 57.6% of students thought online learning during the pandemic is ineffective, more than 70% of students agreed that online learning using eStudy is well-applied in the Argumentative Speaking class and 81% recommended lecturers to use eStudy in the learning process.